Trainee Performance in Loop Electrosurgical Excision Procedure (LEEP) After Simulation Training. Issue 1 (January 2019) - Wilson, Erin; Janssens, Sarah; Ng, Dora; Jolly, Brian; Hewett, David G.; Beckmann, Michael
Abstract : Objective: The aim of the study was to review the performance of trainees in loop electrosurgical excision procedure (LEEP) procedures after the introduction of a simulation training program. Materials and Method: A simulation training program was introduced in September 2016 for gynecology trainees at the study institution. Trainees were encouraged to perform at least 3 simulated LEEP procedures before operating. For a 12-month period after the introduction of training, data on operating time and specimen quality measures of clear margin status, adequate depth, and absence of fragmentation were reviewed. This was compared with a 12-month period before simulation training (from September 2014–September 2015). Trainees were surveyed for feedback on the training. Results: In total, 135 LEEP procedures were reviewed: 68 before and 67 after simulator training. Trainee specimens after training were more likely to be nonfragmented (89.2% vs 55.9%, p = .003), have clear margins (72.2% vs 41.9%, p = .015), and meet "all criteria" (46% vs 20.6%, p = .043) than trainee specimens before training. There was no change in depth adequacy (70.3% vs 67.7%, p = .99). Median trainee procedure time reduced from 18 minutes (interquartile range = 11–24) before training to 8 minutes after training (interquartile range = 6–11) ( p = <0.001). There was no significant change in operating time or specimen quality from LEEP procedures performed by attendings (who did not use the simulator). Trainee and attending procedural outcomes were similar after training. Trainees had mostly positive views on the training, though reported time constraints as a barrier to simulation. Conclusions: After the introduction of an LEEP simulation training program, operative time and specimen quality from trainee procedures seemed to improve.